The Potential Role of Information Technology in Enhancement of Small Enterprise Competitiveness - Denis VASILIEV (Communications of International Proceedings, 2021)
Information technology has dramatically changed competitive landscape in global business environment. Large corporations leverage the power of big data to enhance their strategies. Smaller companies and startups, however, tend to have access to more limited amount of data and often less extensively use digital tools in their daily operations. Limited application of technologies in smaller enterprises may substantially limit their ability to compete with larger competitors. Competition may become even more fierce in the nearest future, given the global nature of competition and rapid development of the technologies. Small companies may be reluctant to use digital tools due to multiple possible reasons. One is lack of relevant skills. The other one is high perceived cost of digital technology integration into existing business models. Finally, lacking recognition of potential benefits that available technologies can bring to small enterprise may demotivate management to apply the technology. Thus, there is a clear need for exploration of all these issues. The article investigates information technology tools available to small companies with limited budgets and demonstrates how this can contribute to securing a sustainable competitive advantage. Skill set essential for implementation of digitalization of smaller companies is also explored. Findings of the present study suggest that digitalization of small businesses is more feasible than it may appear at first. Considering suggestions provided in the article wider uptake of digital technologies among small companies and startups may greatly enhance national economies.
Keywords: data driven management; artificial intelligence; business process automation; machine learning; cloud computing.